(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Steel structures are second most numerous in the stock of existing buildings. In contrast to dominating concrete buildings, they are typically lightweight and are more sensitive to alterations in use or loads. While the sustainability principles require to maintain and keep using these structures, structural assessments often indicate insufficient reliability and need for replacements. The submitted contribution shows that the most important reliability considerations affecting the sustainability of existing steel structures consist of specifying (1) appropriate target reliability level, (2) verification methods, and (3) intervention procedures. The study focuses on the first two aspects. (1) Optimum target reliability can be specified by probabilistic optimisation considering sustainability aspects including structural costs, and expected consequences of replacement and of possible failure. It is shown that lower reliability levels might be considered for the assessment of existing structures than for the design of new structures, with benefits for sustainability in construction. Regarding (2), the most efficient verification methods are based on advanced probabilistic approaches. It is demonstrated that sustainability may be significantly affected by the selection of assessment methods. Advanced reliability approaches commonly reduce assessment requirements by 10–15 %. Sustainability indicators are mostly related to the key aspects (1) and (2). Using the advanced methods may bring a significantly positive contribution to sustainability, particularly when an upgrade of the existing structure is associated with high economic cost and significant environmental impact.